POTENSI ANTIBAKTERI EKSTRAK DAUN PEDADA (SONNERATIA CASEOLARIS) SEBAGAI PENGAWET ALAMI IKAN KEMBUNG (RASTRELLIGER SP) SEGAR - Nirmala Efri Hasibuan; Sumartini Sumartini (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2021)
Preservation is one way to prevent the deterioration of fish quality. This study aims to utilize pedada leaf extract (Sonneratia caseolaris) as a natural preservative in fresh mackerel. This research was divided into three stages, namely sample preparation, pedada leaf extraction and extract application to fish. This study used a completely randomized factorial design consisting of three factors. The first factor was the addition of pedada leaf extract. The second factor is the storage temperature of fish, namely room temperature (23º-27ºC), cold temperature (10ºC), freezing temperature (0ºC). The third factor is storage time, namely 1, 7 and 14 days. Each treatment was repeated twice. Parameters tested include pH value, water content, protein content, total plate number (ALT) and E-coli. The results showed that the addition of pedada leaf extract, differences in storage temperature, and storage time had a significant effect (sig <0.05) on the pH value, water content, protein content and total plate number (ALT). Furthermore, the results of the E-coli test showed that the treatment of cold temperature and freezing temperature on fish with the addition of pedada leaf extract showed negative E-coli content.